Knee joint muscles neuromuscular activity during load-carrying walking - Stastny, Petr; Lehnert, Michal; Zaatar, Amr; Svoboda, Zdenek; Xaverova, Zuzana; Jelen, Karel (Neuro endocrinology letters, 2014)
OBJECTIVE: To investigate the effects of increasing load on changes in the muscle activity ratio and onset of vastus medialis (VM), vastus lateralis (VL) and biceps femoris (BF) during load-carrying walking. MATERIALS AND METHODS: Sixteen strength-trained men performed an isometric test for knee flexion/extension using a dynamometer followed by walking with progressively increasing loads of up to 75% of their body mass (BM). During the isometric tests and load-carrying walking, electromyography (EMG) data were collected from the VM, VL and BF in both legs together with 3D kinematics. RESULTS: Significant changes in the activity ratio were found for the VM/VL (F3,93=5.92, p=0.0001) and VL onset (F3,81=6.8, p=0.0004). Other parameters showed no significant differences. VM/VL was significantly reduced between the 50BM (mean±SD: 0.89±0.4) and the 75BM condition (0.81±0.3). VL onset was significantly accelerated between the BM (26.11±8) compare and the 25% BM (19.47±9), 50% BM (21.21±10) and 75% BM (15.45±6) conditions. CONCLUSION: Load-carrying walking is an exercise and movement activity that increases the activity of VL more than the activity of VM and accelerates the VL action together with the increased load, which can negatively influence knee stability. The VM/VL ratio and onset is equal when walking under weight-bearing conditions. The inter-muscular coordination is changed due to the increased load in complex movements even in individuals with high level of neuromuscular adaptation.
Keywords: odporový trénink; Adult; Electromyography; chůze; Resistance Training; koleno; svalová síla; lidé; Quadriceps Muscle; Walking; biomechanika; čtyřhlavý sval stehenní; Biomechanical Phenomena; Muscle Strength; mužské pohlaví; Knee; Weight-Bearing; elektromyografie; dospělí; Humans; zatížení muskuloskeletálního systému; Male